THE EFFECT OF HEAT TECH THERAPY ON ADOLESCENTS WITH PREMENSTRUAL SYNDROME (PMS) - Sastika Putri, Dhea Regita; Muliani, Rima (Journal of Midwifery Tiara Bunda, 2025)
Background: Adolescence is a phase of life between childhood and adulthood, from the age of 10 to 19 years. Based on the results of research conducted on 3000 women by the Archives of Internal Medicine, it was found that 90% of women experience symptoms of Premenstrual Syndrome (PMS) before the menstrual phase and generally occurs in women aged 14-50 years with symptoms that vary and change in each woman from month to month. Symptoms of Premenstrual Syndrome (PMS) can be different for each woman, even in the same woman the symptoms that arise can be different each menstrual cycle. Women can only experience 1 symptom of Premenstrual Syndrome (PMS) or several symptoms at once. According to the theory of Premenstrual Syndrome (PMS) symptoms that are often experienced by women is lower abdominal pain. Objective: To determine the effect of providing heat tech therapy on adolescents with Premenstrual Syndrome (PMS). Method: This study uses an experimental research design (one group pretest-posttest design). Results: The results of the Wilcoxon Signed Rank Test showed a p-value of 0.004 <0.05, which means that there is an effect of providing heat tech therapy on adolescents with Premenstrual Syndrome (PMS). Conclusion: Heat tech therapy can be used to overcome the symptoms of premenstrual syndrome (PMS), one of which is to relieve lower abdominal pain.